Single-cell ATAC-Seq reveals cell type-specific transcriptional regulation and unique chromatin accessibility in human spermatogenesis. Issue 3 (12th January 2021) - Wu, Xiaolong; Lu, Mujun; Yun, Damin; Gao, Sheng; Chen, Shitao; Hu, Longfei; Wu, Yunhao; Wang, Xiaorong; Duan, Enkui; Cheng, C Yan; Sun, Fei
Abstract: During human spermatogenesis, germ cells undergo dynamic changes in chromatin organization/re-packaging and in transcriptomes. In order to better understand the underlying mechanism(s), scATAC-Seq of 5376 testicular cells from 3 normal men were performed. Data were analyzed in parallel with the scRNA-Seq data of human testicular cells. In all, 10 germ cell types associated with spermatogenesis and 6 testicular somatic cell types were identified, along with 142 024 peaks located in promoter, genebody and CpG Island. We had examined chromatin accessibility of all chromosomes, with chromosomes 19 and 17 emerged as the leading chromosomes that displayed high chromatin accessibility. In accessible chromatin regions, transcription factor-binding sites were identified and specific motifs with high frequencies at different spermatogenesis stages were detected, including CTCF, BORIS, NFY, DMRT6, EN1, ISL1 and GLI3. Two most remarkable observations were noted. First, TLE3 was specifically expressed in differentiating spermatogonia. Second, PFN4 was found to be involved in actin cytoskeletal organization during meiosis. More important, unique regions upstream of PFN4 and TLE3 were shown to display high accessibility, illustrating their significance in supporting human spermatogenesis.